Arnold tongues and the Devil's Staircase in a discrete-time Hindmarsh-Rose neuron model - Felicio C.C.* (2015)
© 2015 Elsevier B.V. All rights reserved.We investigate a three-dimensional discrete-time dynamical system, described by a three-dimensional map derived from a continuous-time Hindmarsh-Rose neuron model by the forward Euler method. For a fixed integration step size, we report a two-dimensional parameter-space for this system, where periodic structures, the so-called Arnold tongues, can be seen with periods organized in a Farey tree sequence. We also report possible modifications in this parameter-space, as a function of the integration step size.